Bedaquiline practice in treatment of extensively drug-resistant mycobacterium tuberculosis in children: Clinical cases - A. A. Akzhigitova; T. N. Ignatova; A. К. Konratov; M. В. Теn (Кубанский научный медицинский вестник)
Background. Bedaquiline is currently a drug of choice in therapy for extensively and multidrug-resistant tuberculosis. It is indicated for children from a 6-year age and young adults as part of a combination chemotherapy, in compliance with the medical council’s (MC) regulation on active extensively and multidrug-resistant tuberculosis.Clinical Cases Description. The article describes the clinical cases of bedaquiline treatment of extensively drug-resistant tuberculosis in сhildren. Patient B., 16 yo, was routinely admitted to a children’s ward of the Orenburg Regional Clinical Antituberculosis Dispensary with the preliminary diagnosis: exudative pleurisy-complicated S1,2 infiltrative focal tuberculosis of left lung. Mycobactérium tuberculósis (MBT) (-). Complaints of cough, painful chest at deep breath, 37.3°C-elevated body temperature. Chest X-ray: left focal shadows in S1,2, intensive homogeneous darkening due to pleural effusion from diaphragm to anterior segment of rib III. An urgent pleural puncture was performed to sample fluid for MBTculture and PCR resistance tests to streptomycin and rifampicin. The patient was treated with anti-tuberculosis drugs according to the IV chemotherapy regimen. Taking into account the MBTculture results, the Medical Board took the decision to start using the V chemotherapy regimen with the inclusion of up to 180 doses of bedaquiline. The patient received anti-TB drugs according to chemotherapy regimen IV. Based on the pleural fluid PCR tests, the MC prescribed a conversion to chemotherapy regimen V with adding bedaquiline up to 180 doses. After 7 months of positive dynamics, the patient was transferred to continuation phase at a children’s sanatorium. Patient S., 10 yo, was routinely admitted to a children’s ward of the Orenburg Regional Clinical Antituberculosis Dispensary with the diagnosis: two-sided bronchopulmonary intrathoracic lymph nodes tuberculosis (ILNTB), calcification phase, MBT (-), follow-up care level I. Given the child’s triple contact with tuberculosis carriers, including extensively drug-resistant (XDR) tuberculosis, the MC prescribed antibacterial drug chemotherapy IF regimen V with adding bedaquiline up to 180 doses: pyrazinamide (Z), prothionamide (Pto), para-aminosalicylic acid (PAS), cycloserine (Cs), bedaquiline (Bq) concurrently with vitamins and hepatoprotectors (ZPtoPASCsBq). After 4 months of positive dynamics, the patient was transferred to anti-bacterial therapy continuation phase 4 (ZPtoCsPAS) for up to 12 months at a children’s sanatorium.Conclusion. The clinical cases presented demonstrate the efficacy of bedaquiline in adolescents having extensively drug-resistant focal pulmonary tuberculosis and intrathoracic lymph nodes tuberculosis. The prescription of bedaquiline in this age cohort requires careful justification and a monitoring of adverse reactions and antituberculosis chemotherapy complications.